DINAMIKA PEMBELAJARAN DENGAN MENGGUNAKAN METODE KOOPERATIF DAN ADAPTIF DALAM UPAYA MENINGKATKAN HASIL BELAJAR SANTRI DI MADRASAH DINIYAH PONDOK PESANTREN NURUL QODIRI - Riki Apriyanto; Ikhwan Aziz Q; Leli Fertiliana Dea (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research is motivated by the gap between traditional learning methods in Madrasah Diniyah and the demands of modern education that emphasize student activeness. The focus of this study is to examine the dynamics of learning through the integration of cooperative and adaptive methods to improve students’ learning outcomes at Madrasah Diniyah Pondok Pesantren Nurul Qodiri, Central Lampung. The research method used is field research with a descriptive qualitative approach. Data were collected through non-participant observation, in-depth semi-structured interviews with educators and students, and documentation, which were then analyzed through stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the learning dynamics at the research site have undergone a positive transformation through a combination of the salafiyah system (sorogan and bandongan) with modern instructional innovations. The implementation of cooperative methods through small group division and adaptive methods through personal guidance has been proven to improve students’ learning outcomes multidimensionally, including cognitive aspects in understanding classical Islamic texts, affective aspects in the courage to express opinions, and social aspects in collaboration. This strategy successfully bridges differences in students’ basic abilities and overcomes linguistic barriers in understanding Arabic-language materials. However, its effectiveness is still constrained by limited time and infrastructure. The conclusion of the study emphasizes that synchronization between pesantren traditions and modern methods creates an inclusive educational ecosystem that is relevant to contemporary developments. This research recommends the need for a more systematic formulation of a “Salaf-Modern” curriculum and strengthening educators’ pedagogical competencies in managing the diversity of students’ learning characteristics to optimize learning efficiency in the future. ABSTRAK Penelitian ini dilatarbelakangi oleh adanya kesenjangan antara metode pembelajaran tradisional di Madrasah Diniyah dengan tuntutan pendidikan modern yang mengedepankan keaktifan peserta didik. Fokus penelitian ini adalah mengkaji dinamika pembelajaran melalui integrasi metode kooperatif dan adaptif untuk meningkatkan hasil belajar santri di Madrasah Diniyah Pondok Pesantren Nurul Qodiri, Lampung Tengah. Metode penelitian yang digunakan adalah penelitian lapangan (field research) dengan pendekatan kualitatif deskriptif. Data dikumpulkan melalui observasi nonpartisipan, wawancara mendalam semi-terstruktur kepada pendidik dan santri, serta dokumentasi, yang kemudian dianalisis melalui tahap reduksi, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa dinamika pembelajaran di lokasi penelitian telah mengalami transformasi positif melalui perpaduan sistem salafiyah (sorogan dan bandongan) dengan inovasi instruksional modern. Penerapan metode kooperatif melalui pembagian kelompok kecil dan metode adaptif melalui bimbingan personal terbukti mampu meningkatkan hasil belajar santri secara multidimensional, meliputi aspek kognitif dalam pemahaman kitab kuning, aspek afektif dalam keberanian berpendapat, serta aspek sosial dalam kerja sama. Strategi ini berhasil menjembatani perbedaan kemampuan dasar santri dan mengatasi hambatan linguistik dalam memahami materi berbahasa Arab. Meskipun demikian, efektivitasnya masih terhambat oleh keterbatasan waktu dan sarana prasarana. Kesimpulan penelitian menegaskan bahwa sinkronisasi antara tradisi pesantren dan metode modern menciptakan ekosistem pendidikan yang inklusif dan relevan dengan perkembangan zaman. Penelitian ini merekomendasikan perlunya formulasi kurikulum